2000
DOI: 10.1007/s004200000167
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between leisure time, physical activities and musculoskeletal symptoms and disability in worker populations

Abstract: Stimulation of leisure time physical activity may constitute one of the means of reducing musculoskeletal morbidity in the working population, in particular in sedentary workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
125
3
13

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(157 citation statements)
references
References 19 publications
11
125
3
13
Order By: Relevance
“…However, it is worth noting that back pain can be caused by a variety of factors (including non-pathological ones). There is an unequivocal differential diagnosis only in a small proportion of back pain cases [29]. The fact that this study is based on self-reported questionnaire data is problematic for another reason: there is always a risk of recall bias for many of the particulars investigated [34].…”
Section: Discussionmentioning
confidence: 96%
“…However, it is worth noting that back pain can be caused by a variety of factors (including non-pathological ones). There is an unequivocal differential diagnosis only in a small proportion of back pain cases [29]. The fact that this study is based on self-reported questionnaire data is problematic for another reason: there is always a risk of recall bias for many of the particulars investigated [34].…”
Section: Discussionmentioning
confidence: 96%
“…7, 11-13, 15, 16, 19, 25-28 Other factors that were hypothesized to contribute to low back pain in truck drivers were sedentarism, improper diet, alcohol consumption, cigarette smoking, improper working conditions and work in excess, since all these characteristics are related to the profile of these professionals and are also related to the presence of low back pain. 18,[29][30][31] The 410 truck drivers were evaluated regarding these factors by questionnaire, and the result was that low back pain was present in 59.0% of these professionals and that among the probable risk factors analyzed, only the number of working hours was significantly correlated with the presence of low back pain.…”
Section: Discussionmentioning
confidence: 99%
“…There were a number of known risk factors for mortality that were unmeasured in the current analysis (e.g. body mass index, smoking) and, while these have been previously associated with pain Hildebrandt et al, 2000;John et al, 2006), it is unlikely that these would be limited to persons with disabling, but not non-disabling, pain. Social class is a strong marker of both body mass index and smoking status (Power et al, 2005) and, therefore, adjusting for social class will have controlled, in part, for the effect of these two potential confounders and such adjustment had little impact on the results.…”
Section: Differences Between Men and Womenmentioning
confidence: 99%